Effective lifetime radiation risk for a number of national mammography screening programmes. Issue 3 (August 2018) - M.Ali, R.M.K.; England, A.; McEntee, M.F.; Mercer, C.E.; Tootell, A.; Hogg, P.
Abstract: Background and purpose: The performance of mammography screening programmes is focussed mainly on breast cancer detection rates. However, when the benefits and risks of mammography are considered, the risk of radiation-induced cancer is calculated for only the examined breast using Mean Glandular Dose (MGD). The risk from radiation during mammography is often described as low or minimal. This study aims to evaluate the effective lifetime risk from full field digital mammography (FFDM) for a number of national screening programmes. Material and Methods: Using an ATOM phantom, radiation doses to multiple organs were measured during standard screening mammography. Sixteen FFDM machines were used and the effective lifetime risk was calculated across the female lifespan for each machine. Once the risks were calculated using the phantom, the total effective lifetime risk across 48 national screening programmes was then calculated; this assumed that all these programmes use FFDM for screening. Results: Large differences exist in effective lifetime risk, varying from 42.21 [39.12–45.30] cases/10 6 (mean [95% CI]) in the Maltese screening programme to 1099.67 [1019.25–1180.09] cases/10 6 for high breast cancer risk women in the United States of America. These differences are mainly attributed to the commencement age of screening mammography and the time interval between successive screens. Conclusions: Effective risk should be considered as an additional parameter for the assessment of screening mammography programme performance, especially for those programmes which recommend an early onset and more frequent screening mammography. Highlights: Effective lifetime risk was used to evaluate the radiation risk from screening mammography. Organs radiation dose were measured inside ATOM phantom using thermoluminescent dosimeters. With regard to radiation risk, major differences were recognised amongst screening programmes.